The Effect of Awareness, Income, and Service Quality on Taxpayer Compliance in Paying Land and Building Tax in Kuningan District - Santi Halimatusadiyah, Dede; Melha, Melha; Firasati, Aoliyah (DINASTI RESEARCH, 2025)
This study looked at how taxpayer compliance with paying Land and Building Tax (PBB) in Kuningan District was impacted by awareness, income level, and service quality. This study employed a quantitative approach using SPSS software version 26 to handle data from multiple linear regression analysis. One hundred randomly chosen respondents (random sampling) from among taxpayers registered with the Kuningan Regency Regional Revenue Agency were given questionnaires in order to collect data. The findings of analysis show that the level of awareness and quality of service contribute significantly to taxpayer compliance in PBB payments. On the other hand, there is no discernible impact of the income variable on the degree of compliance. The government can take these results into account when developing strategies to increase taxpayer compliance, such as by enhancing the standards of public services related to taxes and providing continuous tax education.